136k views
2 votes
Solve.

y/3 - 5 = 4

y =

User Spoida
by
5.0k points

2 Answers

3 votes

Answer:

y = 27

Explanation:

So we have to solve for y in the given equation.


(y)/(3)-5=4

Add 5 to both sides.


(y)/(3)=9

Multiply both sides of the equation by 3.

y = 27

So we have found that y = 27.

I hope you find my answer and explanation to be helpful.

User Toleo
by
4.1k points
5 votes


(y)/(3) - 5 = 4\\\\(y)/(3) \cdot 3 - 5 \cdot 3 = 4 \cdot 3\\ y - 15 = 12\\y = 12 + 15\\y = 27

User Joost Schuur
by
5.3k points